Negotiating Faith and Ethnicity in the Digital Sphere: A Netnographic Analysis of Chinese New Year Discourses on BBC News YouTube - Fani Rahma Sari (Zamzami Scholar Publishing, 2026)
This study examines the digital construction of Chinese Muslim identity regarding the Chinese New Year (Imlek) on the BBC News Indonesia YouTube channel. Synthesizing Stuart Hall’s representation theory with Kozinets’ netnography, this research examines how digital media frames the ethnicity-religion intersection and how virtual audiences decode these meanings. The analysis reveals that while the BBC strategically frames Imlek as cultural heritage compatible with Islam, the comment section functions as a contested “third space.” Digital engagement manifests in three distinct patterns: dominant-hegemonic acceptance, negotiated readings imposing theological boundaries, and oppositional readings rejecting the practice as contrary to Tawhid. Consequently, this study argues that the digital sphere serves as a crucial arena of contestation, where algorithm-driven interactions actively reinforce, challenge, and reshape the public understanding of Chinese Muslim identity in contemporary Indonesia.